PTU-096 Metabolic Bone Disease in Mild Chronic Liver Disease- is it Worth Checking?. (4th June 2013) - Patel, B; McLaughlin, S; Williams, E; Al-Shamma, S
Abstract : Introduction: Liver cirrhosis (LC) is increasing in frequency and can cause significant morbidity including metabolic bone disease (MBD) namely osteopaenia and osteoporosis, risk factors of fractures. It is vital that patients with MBD are identified and commenced on appropriate treatment. Whilst studies have investigated the prevalence of MBD in cirrhotics awaiting transplantation, the exact frequency of MBD in mild LC is not known. We aimed to assess the frequency of MBD in patients with mild LC (MELD score < 16) who had undergone DEXA scanning at our instituation to ascertain whether routine screening is worthwhile. Methods: This was a single-centre retrospective study. From a radiology database, we identified 62 patients with histologically, radiologically and/or clinically diagnosed LC who had undergone a DEXA scan between May 2007 & June 2012. Osteopaenia and osteoporosis were defined using WHO criteria. Contemporaneous bloods were used to calculate the MELD. A similar number of age and sex-matched patients with histologically-confirmed coeliac disease (CD) who had had a DEXA scan were identified to act as a comparison group. The same scanner was used for all patients. Results: Patient characteristics We identified 61 patients with LC and 45 with CD. The most common aetiologies were ALD (52%) and PBC (23%). The mean age for cirrhotics was 60.1 years (range 33–78) with 64% M and 36% F. The mean MELD was 10.7 ± 4.1. For those with CD the mean age was 52 years (range 17–82) with 27% M & 73% F. Patients with osteoporosis & osteopenia Of the cirrhotcis, 57% had MBD (36% osteopenia, 21% osteoporosis) compared to 62% of patients with CD (42% and 20% respectively). 57% of patients with ALD had MBD compared to 71% of patients with PBC. The mean age of those with LC and osteoporosis was 62.4 years (range 47–78) with 54% of patients being male. For those with CD and osteoporosis the mean age was 69 years (range 46–82) with 89% being female. MBD in male ALD patients: Male ALD patients were at particular risk. There was a statistically significantly higher risk of MBD in male ALD patients (77.8%; 55.8–99.8%) compared to male CD patients (32.1%; 13.1–51.2%; P < 0.05.) On the other hand, female CD patients had a satistically greater risk of MBD vs females with ALD. MELD score correlation with T-score: We found no correlation between the MELD score and the lumbar or hip T-score (p = 0.803.) Therefore, DEXA screening should be offered to all LC patients regardless of disease severity. Conclusion: All patients with LC, irrespective of MELD, should undergo DEXA scanning due to the high prevalence of MBD. Male ALD patients warrant particular attention due to the particularly increased risk of MBD and fractures. Disclosure of Interest: None Declared